Growth and enduring epidemic diseases - Bell, Clive; Gersbach, Hans (Working papers of the Center of Economic Research at ETH Zurich, 2006)
This paper studies the formation of human capital and its transmission across generations when premature adult mortality is a salient feature of the demographic landscape, either permanently or in the form of a long-period wave that follows the outbreak of an epidemic. We establish several threshold properties of the model, for such a shock can severely retard economic growth, even to the point of leading to an economic collapse. Premature adult mortality may exacerbate inequality under nuclear family arrangements. Pooling mortality risks with equal treatment of all children may fend off, or even induce, a collapse, depending on the initial conditions and the size and duration of the shock. Awareness campaigns may also trigger a collapse by introducing undesirable expectational feedbacks.
Keywords: Graue Literatur